PENGARUH KEPRIBADIAN TERHADAP KINERJA KARYAWAN DI HOTEL ELRESAS LAMONGAN - Nilawati Fiernaningsih (Politeknik Negeri Malang, 2017)
The purpose of this study to determine the effect of personality on employee performance. The type of research used is quantitative descriptive research. Sampling technique using non probability sampling method with saturated sampling technique that is taking the entire amount of the population to be sampled that is a number of 30 respondents. Methods of data collection by interview, questionnaire and observation. For data analysis used simple linear regression. Based on the analysis of data processing that has been tested in this study stated valid and reliable. The result of simple linear regression equation is Y = 26,309 + 2,061X. Results of the hypothesis test are known to be> ttable> 5,025> 2.048. Coefficient of determination of 0.474. While the percentage of the magnitude of the influence between the variable personality and employee performance variables of 49.2% and the rest of 50.8% influenced by other variables not examined in this study.